A New Drug Combinatory Effect Prediction Algorithm on the Cancer Cell Based on Gene Expression and Dose–Response Curve. (19th February 2015) - Goswami, C Pankaj; Cheng, L; Alexander, PS; Singal, A; Li, L
Abstract : Gene expression data before and after treatment with an individual drug and the IC20 of dose–response data were utilized to predict two drugs' interaction effects on a diffuse large B‐cell lymphoma (DLBCL) cancer cell. A novel drug interaction scoring algorithm was developed to account for either synergistic or antagonistic effects between drug combinations. Different core gene selection schemes were investigated, which included the whole gene set, the drug‐sensitive gene set, the drug‐sensitive minus drug‐resistant gene set, and the known drug target gene set. The prediction scores were compared with the observed drug interaction data at 6, 12, and 24 hours with a probability concordance (PC) index. The test result shows the concordance between observed and predicted drug interaction ranking reaches a PC index of 0.605. The scoring reliability and efficiency was further confirmed in five drug interaction studies published in the GEO database. CPT Pharmacometrics Syst. Pharmacol. (2015) 4, 80–90; doi:10.1002/psp4.9 ; published online on 19 February 2015.